2011
DOI: 10.1111/j.1582-4934.2010.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cyclophilin-D as a potential therapeutic target for post-myocardial infarction heart failure

Abstract: The pharmacological inhibition or genetic ablation of cyclophilin-D (CypD), a critical regulator of the mitochondrial permeability transition pore (mPTP), confers myocardial resistance to acute ischemia-reperfusion injury, but its role in post-myocardial infarction (MI) heart failure is unknown. The aim of this study was to determine whether mitochondrial CypD is also a therapeutic target for the treatment of post-MI heart failure. Wild-type (WT) and CypD–/– mice were subjected to either sham surgery or perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…So-called ischemia-reperfusion damage is believed initiated by a burst of oxygen radicals rapidly produced by mitochondria (Kalogeris et al, 2012; Perrelli, 2011), with some similarity to air BM harvest. Induction of the MPTP is implicated in mechanisms of ischemia-reperfusion damage (Griffiths and Halestrap, 1995; Kim et al, 2003; Lim et al, 2010). This may be similar to what HSCs experience upon harvest in ambient air, with induction of the MPTP via oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…So-called ischemia-reperfusion damage is believed initiated by a burst of oxygen radicals rapidly produced by mitochondria (Kalogeris et al, 2012; Perrelli, 2011), with some similarity to air BM harvest. Induction of the MPTP is implicated in mechanisms of ischemia-reperfusion damage (Griffiths and Halestrap, 1995; Kim et al, 2003; Lim et al, 2010). This may be similar to what HSCs experience upon harvest in ambient air, with induction of the MPTP via oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that mitochondrial dysfunction and reduced ATP production are associated and accelerate the progressive nature of heart failure 22, 23 . Modulation of mitochondrial function reduces the infarct size of the ischemic heart in mice and represents a promising therapeutic strategy for heart failure 2426 . In this context, our findings suggest that loss of NRP-1 in CMs results in significant alterations in mitochondrial homeostasis, which may be due to altered PGC1α and PPARγ expression and eventually lead to cardiomyopathy and increased heart failure after ischemic stress.…”
Section: Discussionmentioning
confidence: 99%
“…The mPTP inhibitors, such as cyclosporin-A (CsA) (153, 154), cyclophilin-D (155), cinnamic anilides (156), and antioxidants are known to prevent the mPTP opening. Yin et al reported a NP system containing CsA which when used in combination with adipose-derived stem cell (ASCs) in a swine model of myocardial infarction showed therapeutic benefits (157).…”
Section: Mitochondrial Targets For Cardiovascular Diseases (Cvd)mentioning
confidence: 99%